The effect of investment experience and financial literacy toward financial behavior on investment decision - Salomo Michihiro Simanjuntak; A. A. Gede Rama Cahyaningrat; Dewa Made Adi Pranayanata Kusuma; I Nyoman Jyobala Wijaya Kanela; Leiviano Aaron Susanto; Farida Komalasari (President University, 2022)
The covid-19 Pandemic made a lot of people work from home. It also made their wages decrease. Because of that, they tried to do something to make more money. From that, the investment and trading trend started to rise in Indonesia. However, not everyone has the same education and experience in investing or trading. From that, this research aims to examine whether investment experience, financial literacy, and financial behavior affect investment decisions or not. This is a quantitative study that uses online questionnaires to collect primary data. The questionnaires were distributed to 151 Indonesians who were chosen using the purposive sampling method. The data were analyzed with the use of the Structural Equation Model (SEM). Financial literacy and investment experience were employed as independent variables; meanwhile, financial behavior and investment decision, on the other hand, are the mediating and dependent variables. As a result, investment experience influences investment decisions indirectly through financial behavior. Same with that, financial literacy also influences investment decisions indirectly through financial behavior. This result could be used by many parties in developing an investment atmosphere in order to increase the investment decision.